2015
DOI: 10.1194/jlr.m058941
|View full text |Cite
|
Sign up to set email alerts
|

Novel function of vitamin E in regulation of zebrafish (Danio rerio) brain lysophospholipids discovered using lipidomics

Abstract: This article is available online at http://www.jlr.org have used zebrafi sh to characterize the molecular consequences of vitamin E defi ciency because zebrafi sh require dietary ␣ -tocopherol, especially during embryonic development ( 2 ). Zebrafi sh also express the ␣ -tocopherol transfer protein ( ␣ -TTP), which facilitates hepatic ␣ -tocopherol secretion into the circulation in humans ( 3 ), and likely facilitates ␣ -tocopherol delivery from the yolk to the developing zebrafi sh embryo ( 4 ). Importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 39 publications
3
52
0
1
Order By: Relevance
“…Lipidomics data processing was performed as described [23,25]. Student’s t -tests (Excel, Microsoft) were used to compare the two VitE groups with statistical significance set at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipidomics data processing was performed as described [23,25]. Student’s t -tests (Excel, Microsoft) were used to compare the two VitE groups with statistical significance set at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…These combined antioxidant deficiencies precluded assessment of neurological and cognitive consequences resulting solely from VitE deficiency. Therefore, in the present study, we investigated the behavioral perturbations of isolated VitE deficiency in adult E− and E+ zebrafish fed diets with adequate ascorbic acid [22,23]. We hypothesized that E− adult zebrafish would display significant cognitive impairments associated with elevated brain lipid peroxidation and, potentially, additional metabolic disruptions, as we reported in VitE-deficient zebrafish embryos [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Choi and co-workers found that low vitamin E concentrations are correlated with a ~60% depletion of 4 DHA-containing phospholipids and 19 lyso phospholipids in zebra fish brains. Due to the decrease of DHA-containing phospholipids in Vitamin E-deficient zebra fish, vitamin E is postulated to play a role in the homeostatic balance of anti-inflammatory and inflammatory lipids in the brain (98). …”
Section: The Roles Of Various Lipid Classes In Disease Pathophysiologiesmentioning
confidence: 99%
“…Although supplements have been found to have benefit in slowing Alzheimer's disease progression, they do not seem to prevent Alzheimer's disease occurrence (Traber 2014). Because 96% of adult women and 90% of men in the United States do not receive adequate levels of vitamin E in their diet (Choi et al 2015), it would seem that additional studies are needed to explore further risk reduction related to the development of cognitive impairment.…”
Section: Healthy Agingmentioning
confidence: 99%
“…In a prospective study carried out in Finland, a sample of 140 over 65-year-olds with no memory impairment at the onset of the study was followed for 8 years, during which time it was found that higher total serum levels of vitamin E (alpha-tocopherol), as well as the other forms of the vitamin, seemed protective against memory disorders (Mangialasche et al 2013). A recent study, using a zebra fish model, showed that a diet deficient in vitamin E-equivalent to a human lifelong deficiency-resulted in about 30% lower levels of DHA phosphatidylcholine (DHA-PC), which is a part of the cellular membrane in every brain cell or neuron, indicating that DHA-PC may be a good predictor of a higher risk for Alzheimer's disease (Choi et al 2015). A recent meta-analysis found that patients with Alzheimer's disease, compared with cognitively intact elderly controls, had significantly lower plasma alphatocopherol concentrations (Lopes da Silva et al 2013).…”
Section: Healthy Agingmentioning
confidence: 99%